Nonlinear two conformable fractional differential equation with integral boundary condition - DJIAB, Somia; NOUIRI, Brahim (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
This paper deals with a boundary value problem for a nonlinear differential equation with two conformable fractional derivatives and integral boundary conditions. The results of existence, uniqueness and stability of positive solutions are proved by using the Banach contraction principle, Guo-Krasnoselskii’s fixed point theorem and Hyers-Ulam type stability. Two concrete examples are given to illustrate the main results. Mathematics Subject Classification (2010): 47H10, 26A33, 34B18. Received 25 February 2020; Revised 29 February 2020. Published Online: 2023-03-20. Published Print: 2023-04-30